2006
DOI: 10.1007/s11430-006-0518-y
|View full text |Cite
|
Sign up to set email alerts
|

Paleoenvironments indicated by the fossil mammalian assemblages from red clay-loess sequence in the Chinese Loess Plateau since 8.0 Ma B.P.

Abstract: Information from eleven profiles of eolian earthy red silty clay and loess of the middle of the Late Miocene to Holocene age have been studied and correlated. A complete summary profile with projected isotopic ages and fossil-bearing beds has been assembled. The profile is subdivided into 12 stratigraphic units proceeding from the lower (older) to the upper (younger) one. The character of mammalian assemblages contained in each unit was analyzed and the corresponding paleo-climatic environments were deduced. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…elements, such as Macaca and Sivapanthera [11] . The warm-adapted mammals dominated assemblage of the Gongwangling Fauna conflicted with the result from the study on the non-biological indices which indicated that the L15 should be deposited under dry and cold conditions [68] . It is worth mentioning that all the examples of the warm-adapted mammals preserved in loess are located on the edge of the Loess Plateau, especially the Gongwangling Fauna is near the transitional zone.…”
Section: Figurementioning
confidence: 89%
“…elements, such as Macaca and Sivapanthera [11] . The warm-adapted mammals dominated assemblage of the Gongwangling Fauna conflicted with the result from the study on the non-biological indices which indicated that the L15 should be deposited under dry and cold conditions [68] . It is worth mentioning that all the examples of the warm-adapted mammals preserved in loess are located on the edge of the Loess Plateau, especially the Gongwangling Fauna is near the transitional zone.…”
Section: Figurementioning
confidence: 89%
“…The Renjiapo fauna at 3.4 Ma mainly are composed of even-toed ungulates, with a predominance of hypsodont animals. Their signatures represent grassland expansion and a cool-dry climate [37,38].…”
Section: Other Evidence For Paleoclimate Change During the Pliocenementioning
confidence: 99%
“…Vegetation shifted at the same time to grassland or desert steppe, indicating a cold and dry climate [31]. Other fossils in various locations on the CLP indicate that vegetation shifted from open forest-steppe in the Pliocene to shrub steppe in the early Pleistocene, and then later into steppe or desert [32]. All indicators show that climate was more humid in the early Pleistocene than in the late Pleistocene, although was somewhat drier than that of the Pliocene.…”
Section: Stronger Summer Monsoon In Early Pleistocenementioning
confidence: 99%